An Analysis of Factors Affecting Consumer Intentions Toward Green Products - Ika Wulandari Ridwan (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2026)
This study aims to examine the factors influencing consumers’ intention to use green products. A quantitative research approach was employed, involving 300 respondents who are users of Philips MyCare LED Bulb products. Data were analyzed using descriptive statistical analysis, Structural Equation Modeling (SEM), and Partial Least Squares (PLS). The results indicate that social approval has a positive effect on consumer attitudes and also positively influences behavioral intention. Ease of use has a positive and significant effect on consumer attitudes; however, its effect on behavioral intention is positive but not significant. Perceived risk is found to have a positive effect on both consumer attitudes and behavioral intention. Furthermore, consumer attitude has a positive and significant effect on behavioral intention. These findings provide insights into the key determinants of consumer intention in adopting environmentally friendly products, highlighting the importance of social influence, usability, and perceived risk in shaping attitudes and behavioral intentions.